Emotional Competencies and Entrepreneurial Intention: An Extension of the Theory of Planned Behavior - Verdesoto Velástegui, Oswaldo Santiago (Pontificia Universidad Católica del Perú, 2021)
This study analyzed the relationship between emotional competencies and entrepreneurial intention in final-year undergraduate students of public higher education institutions in Ecuador, supported by an extended model of Ajzen's Theory of planned behavior (1991). The results were derived from a questionnaire applied to students in the last semester of degrees involving academic business training. To analyze the results, structural equation modeling (SEM) was used. The findings show that emotional competencies are significant factors in the configuration of entrepreneurial intentions and have a direct and positive relationship with their cognitive precursors: entrepreneurial attitude and self-efficacy. It is suggested that students with a higher degree of emotional competencies cope better with the cognitive bias that can make it difficult to recognize business opportunities. The main contribution of this study was to generalize the results that have been obtained in the use of emotional competencies to promote the intentionality of entrepreneurship in the contexts of emerging economies.

Este estudio analizó el poder explicativo de las competencias emocionales y su relación con la intención emprendedora de los estudiantes de pregrado de último año de las instituciones de educación superior públicas de Ecuador, respaldados por un modelo extendido de la teoría del comportamiento planificado de Ajzen (1991). Los resultados se derivaron de un cuestionario dirigido a estudiantes del último semestre de las carreras con formación académica empresarial los cuales fueron sometidos a análisis de ecuaciones estructurales (MES). Los hallazgos mostraron que las competencias emocionales son factores significativos en la configuración de las intenciones emprendedoras y su relación directa y positiva con los antecedentes cognitivos de la actitud empresarial y a la autoeficacia. Se sugiere que los estudiantes con mayor grado de competencias emocionales enfrentan de mejor manera el sesgo cognitivo que puede dificultar el reconocimiento de oportunidades empresariales. La principal contribución de este estudio fue dar mayor generalidad a los resultados que se han obtenido en el uso de las competencias emocionales para fomentar la intencionalidad de emprendimiento en contextos de economías emergentes.
Keywords: Inteligencia emocional; Educación superior--Ecuador; Emprendedores--Competencias; Autoeficacia; http://purl.org/pe-repo/ocde/ford#5.02.04